Forensic accounting and its role in reducing financial corruption: A field study applied on some judicial institutions in the Kingdom of Saudi Arabia - Abdallah, Mohammed Elsadig (Journal of Economic, Administrative and Legal Sciences, 2024)
The problem of the study represented in the increase of a financial nature’s disputes in judicial institutions in many countries, as a result of financial corruption and the prioritization of the personal interests over the public interest, and the need of these institutions for forensic accounting to help them decide on these cases. The study basically aimed to determine the role of forensic accounting in reducing financial corruption, and to know the qualifications, skills and qualities that a forensic accountants must possess and the nature of the information that they must provide to judicial institutions when needed. The questionnaire used to collect data from some judicial institutions in the Kingdom of Saudi Arabia, therefore (100) questionnaires were distributed and (100%) collected and analyzed. The study findings showed that, the forensic accountant uses the diagnostic methods to conduct tests to determine the risks resulting from fraud, which leads to reducing the practice of bribery to obtain undeserved privileges, and the forensic accountant’s understanding of courtroom procedures enables him to provide information that contributes to reducing financial corruption. The study recommended the need to enact more legislation to tighten penalties for those who commit financial corruption crimes that are discovered by forensic accounting in the Kingdom of Saudi Arabia.